Interaction between myofibroblasts and stem cells in the fibrotic heart: balancing between deterioration and regeneration. (27th February 2014) - Ramkisoensing, Arti A.; de Vries, Antoine A.F.; Atsma, Douwe E.; Schalij, Martin J.; Pijnappels, Daniël A.
Abstract: Signalling between the various cell types in the heart has been investigated for decades. However, relatively little is known about the interplay between the cardiac fibroblasts and myofibroblasts, which help to maintain myocardial tissue structure and function, and resident cardiac or extracardiac stem cells involved in tissue homeostasis and repair. Much of our knowledge about these interactions is derived from experimental animal models, especially those of myocardial infarction and stem cell transplantation. However, it still remains incompletely understood how stem cell therapy could modulate cardiac fibrosis in a beneficial manner and, how on the other hand, fibrotic processes in the heart may affect the therapeutic potential of stem cell therapy. A detailed and mechanistic insight into these matters would expedite the therapeutic optimization of cardiac cell therapy for the fibrotic heart and may even provide a basis for future biological therapies aiming for a reversal of cardiac fibrosis. Therefore, the main focus of this review is to discuss interactions between myofibroblasts and stem cells, especially in the adult and diseased, fibrotic myocardium, and emphasize those aspects that require more investigation using dedicated models and tools.